Yeasts from Iranian traditional milk kefir samples: isolation, molecular identification and their potential probiotic properties. (6th August 2022) - Rahmani, B.; Alimadadi, N.; Attaran, B.; Nasr, S.
Abstract: Milk kefir is a fermented dairy product with numerous attributed health benefits due to the presence of a complex eukaryotic and prokaryotic microbiota. In this study, a total number of 26 yeast isolates were obtained from eight kefir samples from three different cities of Iran. The isolates belonged to Kluyveromyces marxianus, Saccharomyces cerevisiae, Pichia fermentans and P. kudriavzevii . The potential probiotic characteristics of the isolates were evaluated based on their ability to tolerate the stimulated condition of the gastrointestinal tract. In addition, hemolytic activity, adherence to different solvents, auto‐aggregation, adhesion to the epithelial intestine‐derived cells and antimicrobial activity of the selected isolates were evaluated. Overall, four yeast strains (three strains of S. cerevisiae and one strain of P. fermentans ) showed resistance and survival ability against the gastrointestinal physiological conditions including acidic pH, presence of bile salt and digestive enzymes. They were able to grow at 37°C and had the capacity to adhere to epithelial intestine‐derived cells. These results suggest that the selected strains can be proper candidates as probiotic yeast strains for the development of novel functional foods. Abstract : Significance and Impact of the Study: This study revealed the diversity of yeasts in some traditional kefir samples from Iran. Kluyveromyces marxianus was the dominant yeast species followed by Saccharomyces cerevisiae, P. fermentans and P. kudriavzevii . Three isolates of S. cerevisiae and one isolate of P. fermentans were exhibited high abilities of adherence to different solvents and auto‐aggregation and acceptable adhesion to the epithelial intestine‐derived cells but no antimicrobial activity against investigated pathogens. Although further studies on their health benefits and in vivo trials are required, these findings suggest that the yeast isolates can be considered as possible probiotic candidates for the development of novel functional foods.